From shadowing to active learning: exploring the impact of supervised teaching clinics on gynecology education - Sangsang Ren; Hong Zhan; Asanga Fernando; Asanga Fernando; Xiangrong Xu; Weiguo Lu (Frontiers in Medicine, 2025)
BackgroundSupervised Teaching Clinics (STCs) have emerged as an innovative approach to medical education, particularly in specialties like gynecology, where hands-on experience is crucial. Traditional clinical rotations often leave students in passive roles, limiting their active participation and the development of essential clinical skills.AimThis study aimed to evaluate the impact of STCs on the clinical competencies and professional development of medical students within a gynecological clinic, comparing the outcomes with those of traditional clinic shadowing.MethodsA total of 144 fifth-year medical students were randomly assigned to either a control group, which participated in traditional clinic shadowing, or an STC group, which engaged in both shadowing and supervised teaching activities. The study utilized the Generalized Self-Efficacy Scale (GSES) and the mini-Clinical Evaluation Exercise (mini-CEX) to assess clinical performance. Feedback was also collected from students, tutors, and patients to gage satisfaction and perceived effectiveness.ResultsStudents in the STC group demonstrated significantly higher improvements in clinical skills, particularly in medical interviewing, counseling, and overall clinical competence, compared to the control group. The STC group also reported greater satisfaction with their learning experience, citing enhanced confidence and a deeper understanding of gynecological practice. Tutors and patients provided positive feedback, noting the STC’s role in fostering effective student-patient interactions and comprehensive learning.ConclusionThe structured design of the STC, with a focus on goal direction, relationships, and supporting services, significantly improved educational outcomes in gynecology. By fostering active learning and delivering constructive feedback, STCs effectively enhance students’ clinical competencies and professional development. The study suggests that integrating STCs into traditional clinical education models could substantially optimize medical training.